Antiplatelet therapy in patients with myocardial infarction with non-obstructive coronary arteries: A clinical perspective - Chen, Wenjie; Jiang, Yufeng; Chen, Tan; Zhou, Yafeng (Frontiers in Cardiovascular Medicine, 2023)
Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a heterogeneous group of diseases with different pathological mechanisms, and it is uncertain whether the classical secondary prevention and treatment strategies for myocardial infarction in obstructive coronary artery disease (MI-CAD) are appropriate for patients with MINOCA. Therefore the choice of antiplatelet agents and the therapeutic effect may vary depending on the etiology and pathophysiological mechanisms of MINOCA. This requires our clinical and scientific researchers to properly design prospective studies to explore the pathophysiology of MINOCA and its corresponding etiology in greater depth, so as to understand the effectiveness and safety of medical therapies for different etiologies of MINOCA. Although the current observational studies do not show an obvious beneficial effect of antiplatelet therapy on MINOCA. We are eager to conduct specific prospective randomized controlled trials of antiplatelet agents to assess the specificity, efficacy and safety of different types of antiplatelet agents in patients with MINOCA of different etiologies.